Accounting for the role of hematocrit in between‐subject variations of MRI‐derived baseline cerebral hemodynamic parameters and functional BOLD responses - Xu, Feng; Li, Wenbo; Liu, Peiying; Hua, Jun; Strouse, John J.; Pekar, James J.; Lu, Hanzhang; van Zijl, Peter C.M.; Qin, Qin (Human brain mapping, 2018)
Baseline hematocrit fraction (Hct) is a determinant for baseline cerebral blood flow (CBF) and between‐subject variation of Hct thus causes variation in task‐based BOLD fMRI signal changes. We first verified in healthy volunteers (n = 12) that Hct values can be derived reliably from venous blood T1 values by comparison with the conventional lab test. Together with CBF measured using phase‐contrast MRI, this noninvasive estimation of Hct, instead of using a population‐averaged Hct value, enabled more individual determination of oxygen delivery (DO2), oxygen extraction fraction (OEF), and cerebral metabolic rate of oxygen (CMRO2). The inverse correlation of CBF and Hct explained about 80% of between‐subject variation of CBF in this relatively uniform cohort of subjects, as expected based on the regulation of DO2 to maintain constant CMRO2. Furthermore, we compared the relationships of visual task‐evoked BOLD response with Hct and CBF. We showed that Hct and CBF contributed 22%–33% of variance in BOLD signal and removing the positive correlation with Hct and negative correlation with CBF allowed normalization of BOLD signal with 16%–22% lower variability. The results of this study suggest that adjustment for Hct effects is useful for studies of MRI perfusion and BOLD fMRI. Hum Brain Mapp 39:344–353, 2018. © 2017 Wiley Periodicals, Inc.